THE ROLE OF E-GOVERNMENT ANALYSIS IN SUPPORTING PUBLIC TRUST AND INFORMATION DISCLOSURE IN THE CITY OF KENDARI - Adrian Tawai (DIA: Jurnal Administrasi Publik, 2020)
The uniqueness of this research is the efforts of the Kendari City Government to realize public trust and information disclosure based on the principles of good governance. the purpose of this study is to describe the use of the Kendari City Government website as a means of providing public information. The research method is by observation and interviews with users of the Kendari city website.the results showed that the kendari city website is an online public information forum related to transparency, the government's official agenda, data banks, and news covering the performance of the Kendari City Government's performance. In addition, the commitment of the Mayor of Kendari's commitment to support the availability of online services to realize good governance and accountability. limitations in the use of online services are the lack of experts or human resources in the IT field who are placed to manage the website, have not maximized the performance of PPID in formulating and stating information that causes information flow to the website and the absence of legal instruments both in the text and context regulate the existence of the Kendari City Government website.